2004
DOI: 10.4049/jimmunol.173.6.4154
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Polymorphonuclear Leukocytes Functions by the Neuropeptide Pituitary Adenylate Cyclase-Activating Polypeptide after Activation of MAPKs

Abstract: Anti-inflammatory activities of pituitary adenylate cyclase-activating protein (PACAP) are mediated in part through specific effects on lymphocytes and macrophages. This study shows that in human polymorphonuclear neutrophils (PMNs), PACAP acts as a proinflammatory molecule. In PMNs, vaso-intestinal peptide/PACAP receptor 1 (VPAC-1) was the only receptor found to be expressed by RT-PCR. Using VPAC-1 Ab, we found that VPAC-1 mRNA was translated into proteins. In PMNs, PACAP increases cAMP, inositol triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 60 publications
2
39
1
Order By: Relevance
“…These data suggest that PACAP27 specifically stimulates human neutrophils. In view of the fact that VPAC1 can be stimulated by VIP or PACAP38, as well as by PACAP27, our results were not consistent with those of a previous report which suggested that VPAC1 functions as a PACAP receptor in neutrophils (15). These data suggest that another receptor may be involved in the process of PACAP27-induced intracellular signaling in human neutrophils.…”
Section: Pacap27 Specifically Stimulates Intracellular Signaling In Hcontrasting
confidence: 57%
See 4 more Smart Citations
“…These data suggest that PACAP27 specifically stimulates human neutrophils. In view of the fact that VPAC1 can be stimulated by VIP or PACAP38, as well as by PACAP27, our results were not consistent with those of a previous report which suggested that VPAC1 functions as a PACAP receptor in neutrophils (15). These data suggest that another receptor may be involved in the process of PACAP27-induced intracellular signaling in human neutrophils.…”
Section: Pacap27 Specifically Stimulates Intracellular Signaling In Hcontrasting
confidence: 57%
“…2E), but failed to inhibit PACAP27-induced cAMP elevation (Fig. 2G), indicating that WRW4 does not affect VPAC1, which has been reported to be expressed in human neutrophils (15). ERK phosphorylation was also completely inhibited by pretreating with WRW4, indicating that this ERK phosphorylation is also a part of the FPRL1-dependent signaling cascade (Fig.…”
Section: Pacap27 Uses Fprl1 As a Specific Receptormentioning
confidence: 73%
See 3 more Smart Citations